Chondrocalcinosis is associated with increased knee joint degeneration over 4 years: data from the Osteoarthritis Initiative. Issue 2 (February 2020) - Foreman, S.C.; Gersing, A.S.; von Schacky, C.E.; Joseph, G.B.; Neumann, J.; Lane, N.E.; McCulloch, C.E.; Nevitt, M.C.; Link, T.M.
Summary: Objective: To determine if presence of calcium-containing crystals (CaC) is associated with increased knee joint degeneration over 4 years and assess if total number of CaCs deposited is a useful measure of disease burden. Design: Seventy subjects with CaCs in right knees at baseline were selected from the Osteoarthritis Initiative and matched to 70 subjects without evidence of CaCs. T1-weighted gradient-echo sequences were used to confirm presence of CaCs and count the numbers of distinct circumscribed CaCs. Morphological abnormalities were assessed at baseline and 4-year follow-up using the modified semi-quantitative Whole-Organ Magnetic Resonance Imaging Score (WORMS). Linear regression models were used to analyze the associations between presence of CaCs at baseline and changes in WORMS and to analyze the associations between numbers of circumscribed CaCs at baseline and changes in WORMS. Results: Presence of CaCs was associated with increased cartilage degeneration in the patella (coefficient: 0.33; 95% confidence interval (CI): 0.04–0.63), the medial femur (coefficient: 0.51; 95% CI: 0.18–0.83), the lateral tibia (coefficient: 0.36; 95% CI: 0.01–0.71) as well as the medial and lateral meniscus (coefficient: 0.38; 95% CI: 0.00–0.75 and coefficient: 0.72; 95% CI: 0.12–1.32). Knees with higher numbers of CaCs had increased cartilage degeneration in the patella and medial femur (coefficient: 0.09; 95% CI: 0.05–0.14; P  < 0.001 and coefficient: 0.08; 95% CI: 0.02–0.14; P  = 0.005). Conclusions: CaCs were associated with increased cartilage and meniscus degeneration over a period of 4 years. Assessing the number of CaC depositions may be useful to evaluate risk of onset and worsening of degenerative disease.